Understanding the "extracorporeal membrane oxygenation gap" in veno‐arterial configuration for adult patients: Timing and causes of death. Issue 10 (6th July 2021) - Makhoul, Maged; Heuts, Samuel; Mansouri, Abdulrahman; Taccone, Fabio Silvio; Obeid, Amir; Mirko, Belliato; Broman, Lars Mikael; Malfertheiner, Maximilian Valentin; Meani, Paolo; Raffa, Giuseppe Maria; Delnoij, Thijs; Maessen, Jos; et al.
Abstract: Timing and causes of hospital mortality in adult patients undergoing veno‐arterial extracorporeal membrane oxygenation (V‐A ECMO) have been poorly described. Aim of the current review was to investigate the timing and causes of death of adult patients supported with V‐A ECMO and subsequently define the "V‐A ECMO gap, " which represents the patients who are successfully weaned of ECMO but eventually die during hospital stay. A systematic search was performed using electronic MEDLINE and EMBASE databases through PubMed. Studies reporting on adult V‐A ECMO patients from January 1993 to December 2020 were screened. The studies included in this review were studies that reported more than 10 adult, human patients, and no mechanical circulatory support other than V‐A ECMO. Information extracted from each study included mainly mortality and causes of death on ECMO and after weaning. Complications and discharge rates were also extracted. Sixty studies with 9181 patients were included for analysis in this systematic review. Overall mortality was 38.0% (95% confidence intervals [CIs] 34.2%‐41.9%) during V‐A ECMO support (reported by 60 studies) and 15.3% (95% CI 11.1%‐19.5%, reported by 57 studies) after weaning. Finally, 44.0% of patients (95% CI 39.8‐52.2) were discharged from hospital (reported by 60 studies). Most common causes of death on ECMO were multiple organ failure, followed by cardiac failure and neurological causes. More than one‐third of V‐A ECMO patients die during ECMO support. Additionally, many of successfully weaned patients still decease during hospital stay, defining the "V‐A ECMO gap." Underreporting and lack of uniformity in reporting of important parameters remains problematic in ECMO research. Future studies should uniformly define timing and causes of death in V‐A ECMO patients to better understand the effectiveness and complications of this support.